2001
DOI: 10.1143/jjap.40.l586
|View full text |Cite
|
Sign up to set email alerts
|

1.3–1.6-µm-Wavelength Quantum Dots Self-Formed in GaAs/InAs Short-Period Superlattices Grown on InP (411)A Substrates

Abstract: (GaAs)2(InAs)2 short-period superlattices (SLs) were grown on InP (411)A substrates by gas-source molecular-beam epitaxy. Scanning tunneling microscopy observations revealed that the lateral-composition-modulated quantum dot structures were self-formed. They were aligned periodically along two perpendicular lateral directions with a lateral density of approximately 1011 cm-2. Multilayer quantum dot structures sandwiched between InP barrier layers showed strong photoluminescence emission with wavelengths of 1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…1, the average dot density in a layer is about cm . This is among the highest values that have been achieved for GaAs-based QD optoelectronic devices emitting at greater than 1300 nm [23]- [26]. The amplifier was fabricated using tilted ridge waveguide geometry.…”
Section: Resultsmentioning
confidence: 98%
“…1, the average dot density in a layer is about cm . This is among the highest values that have been achieved for GaAs-based QD optoelectronic devices emitting at greater than 1300 nm [23]- [26]. The amplifier was fabricated using tilted ridge waveguide geometry.…”
Section: Resultsmentioning
confidence: 98%
“…We have already reported that the high lateral density ($10 11 cm À2 ) and well-aligned QD structures were selfformed in (GaAs) m (InAs) n short period SLs grown on InP(411) substrates by gas source MBE. 5) We have already demonstrated that the 1300-1600 nm wavelength selfformed QDs are fabricated by growing the GaAs/InAs short period SLs on InP(411)A substrates and that the wide and precise photoluminescence (PL) emission wavelength control is possible by regulating the SL period and the InAs monolayer (ML) number. 6) We have already reported their good optical properties and fabricated the light emitting diodes (LEDs) with these QDs as an active layer.…”
mentioning
confidence: 99%